Knowledge and practice of family planning methods among married women of reproductive age of Kakani VDC, Nuwakot district, Nepal - K. Sushmita; K. Kshitij (Al Ameen Medical College, 2016)
Background: Family Planning is a way of thinking and living that is adopted voluntarily to contribute effectively to the social development of a country. CPR of Nuwakot district is less than that of National level. The Objective of the study was to assess the knowledge and practice on family planning methods among married women of Kakani VDC. Methods: Descriptive cross-sectional study design was done with quantitative methods. Likewise, PPS sampling procedure was used and sample size was 109. Structured questionnaires as a tool and Interview technique was used to obtain necessary information. Data was entered and analysed through SPSS, and computed mean, standard deviation, tables, cross tabulation and chi - square. Results: The study shows that more than one fifth of the respondents (23.9%) were of age group 28-32 years and more than half of the respondents (51.4%) had marriage at the age of 15-19 years. Depo-Provera was the device known by all respondents and Implant was the least known device. However, more than half (56.9%) MWRAs had good knowledge on family planning and 51.38% of respondents were currently using FP devices. Despite more good knowledge towards family planning use of FP devices is low. Conclusion: The study population had good knowledge towards FP devices; however the use of FP devices was low. It was mainly due to husband being abroad and side effects of the devices.